Primary Osseous Lesions of the Jaws in Iranian population: A study based on biopsy material over a 19-year period - Atarbashi Moghadam, Dr.Saede; Zargooshi, Sepideh (Journal of Dental School, 2023)
Introduction: Intraosseous pathological lesions of the jaw include a wide range of benign to aggressive or malignant lesions with different clinical and histopathological characteristics and require various treatments. This study was designed to assess the frequency and characteristics of primary jaw lesions in a defined group of an Iranian population. Materials and Methods: In this retrospective study, 6676 biopsy reports from the Oral and Maxillofacial Pathology Department, Shahid Beheshti University of Medical Sciences, were assessed. In cases with primary jaw lesions, other variables such as age, gender, location of lesions, and microscopic diagnosis were recorded. The lesions were categorized into “benign /malignant” and “inflammatory” /“non-inflammatory” groups. Chi-square, Kruskal-Wallis, Fisher exact, and T-test were used for statistical analysis. Results: In total, 395 (5.91%) cases had a primary osseous lesion (63.70% female, 36.29% male) with a mean age of 32.37±16.94. About 74% of the lesions were found in the mandible with posterior predilection. Fibro-osseous lesions (27.03%), Central Giant Cell Granuloma (22.57%), and Osteomyelitis (9.18%) were the most common histopathologic diagnosis. The most common malignant tumor was Osteosarcoma (8.61%). Of the total lesions, 10.2% were inflammatory lesions. The most common lesions in children and adolescents were fibro-osseous lesions (24.7%), central giant cell granuloma (24.7%), and simple bone cysts (18.8%). Conclusion: Fibro-osseous lesions and central giant cell granuloma were the most common primary osseous lesions of the jaw in older adults and children with a female predilection. Malignancies included about 9% of all lesions. This study provides a large collection of demographic and microscopic data on primary osseous lesions that will help in accurate diagnosis and appropriate treatment of these lesions.